Effect of Nanoparticles on Wire Surface Coating Using Viscoelastic Third-Grade Fluid as a Coating Polymer inside Permeable Covering Die with Variable Viscosity and Magnetic Field. (6th May 2022) - Khan, Zeeshan; Khan, Ilyas; Ahammad, N. Ameer; Basha, D. Baba; Andualem, Mulugeta
Abstract : Goal . The parameters of coated wire products are determined by momentum and heat transmission inside dies. As a consequence, it is essential to understand the polymerization movement, heat mass transmission, and wall stress concentration. The wire covering technique necessitates a boost in thermal efficiency. As a result, the goal of this study is to see how nanomaterials affect the heat and mass transfer mechanisms of third-grade liquid in wire coating analysis. The Buongiorno model is adopted for nanofluids. Methodology/approach . Continuity, momentum, energy, and nanoparticle volume fraction concentration is used to establish the governing equations. For highly nonlinear, the numerical methodology bvph2 technique is applied to yield numerical solutions. The impacts of the input parameters on motion, temperature, and volume fraction are examined using pictorial representations. Moreover, using the ND-solve, the numerical results are validated analytically. Findings . In Reynolds Modeling, the stress on the entire wire surface integrated shear forces at the surface dominate Vogel's model, according to the analytical conclusions of this inquiry. It is observed that the nanomaterials appear to have a favorable impact on wire force throughout the entire surface and shear forces at the surface. The polymer velocity can be increased using a non-Newtonian parameter. The temperature profile is increased in the first half of the segment with larger values of random motion and nonlinear thermal while decreases in the later part. In addition, the Brownian motion component raises the concentration profile, but the thermophoresis factor decreases it. Practical implications . This research could aid in the advancement of wire coating technologies. Originality/value . For the first time, Brownian motion with generation/absorption slippage processes is used to investigate the importance of nanoparticles in wire coating assessment. Two different models are utilized for time-dependent viscosity: Reynolds and Vogel models.